Living Qur'an melalui Praktik Quran Journaling: Studi Netnografi pada Akun Instagram @helmpaperco - Al Rifai, Agna Fikri; El-Hakim, Abdul Halim; Azhim, Ahmad Fauzan; Nahilda, Asya Fauzul; Ismail, Ecep; Muhyi, Asep Abdul (Jurnal Penelitian Multidisiplin Ilmu, 2025)
This study explores the practice of Qur’an Journaling on the Instagram account @helmpaperco as a manifestation of Living Qur’an in the digital culture. Utilizing a qualitative approach with etnographic methods, this research finds that digital journaling activities create a reflective and spiritual space that strengthens personal connections with the Qur’an. This practice is characterized by users' emotional and intellectual engagement, as well as thematic and adabi-ruhi interpretations. These findings indicate that social media can serve as an effective medium for contextual and participatory engagement with the values of the Qur’an.